Children's rates of BMI change during pre‐pandemic and two COVID‐19 pandemic periods, IQVIA Ambulatory Electronic Medical Record, January 2018 Through November 2021. Issue 3 (1st February 2023) - Pierce, Samantha Lange; Kompaniyets, Lyudmyla; Freedman, David S.; Goodman, Alyson B.; Blanck, Heidi M.
Abstract: Objective: Many US youth experienced accelerated weight gain during the early COVID‐19 pandemic. Using an ambulatory electronic health record data set, the authors compared children's rates of BMI change in three periods: pre‐pandemic (January 2018‐February 2020), early pandemic (March‐December 2020), and later pandemic (January‐November 2021). Methods: This study used mixed‐effects models to examine differences in rates of change in BMI, weight, and obesity prevalence among the three periods. Covariates included time as a continuous variable, a variable indicating in which period each BMI was taken, sex, age, and initial BMI category. Results: In a longitudinal cohort of 241, 600 children aged 2 through 19 years with ≥4 BMI measurements, the monthly rates of BMI change (kilograms per meters squared) were 0.056 (95% CI: 0.056‐0.057) in the pre‐pandemic period, 0.104 (95% CI: 0.102‐0.106) in the early pandemic, and 0.035 (95% CI: 0.033‐0.036) in the later pandemic. The estimated prevalence of obesity in this cohort was 22.5% by November 2021. Conclusions: In this large, geographically diverse cohort of US youth, accelerated rates of BMI change observed during 2020 were largely attenuated in 2021. Positive rates indicate continued weight gain rather than loss, albeit at a slower rate. Childhood obesity prevalence remained high, which raises concern about long‐term consequences of excess weight and underscores the importance of healthy lifestyle interventions.